(untitled) - Droblas, Adele (New York, NY, 2003)
100 percent of what people need to master the latest version of the world's most popular digital video editing application, covers the brand-new release of Adobe Premiere, including all of the latest features, offers tutorials, tips, and tricks for editing video in Premiere as well as how to create special effects in Premiere, After Effects, Electrifier and other applications, and demonstrates how to integrate narration, music, and sound effects with moving images like a pro. Its CD-ROM contains video-based tutorials, a library of usable video clips and sample effects, useful video filters and utilities, and Premiere tryouts for both Mac and Windows.
Keywords: Motion pictures,Digital video,Phim kỹ thuật số,Ảnh động; Editing,Data processing,Editing,Data processing,Xử lý dữ liệu,Biên soạn,Biên soạn,Xử lý dữ liệu